Nevus sebaceus of Jadassohn: an unusual case report with review of literature - Sahu, Shilpi; Agarwal, Akshay; Dhar, Reeta (International Journal of Research in Medical Sciences, 2016)
A 16-year-old girl presented with a new, rapidly growing, raised, hypopigmented, cerebriform plaque on the scalp. The skin lesion was brown coloured and with a waxy aspect. The diagnosis ’nevus sebaceus’ was established. Nevus sebaceous of Jadassohn is a hamartoma with a combination of abnormalities of the epidermis, hair follicles, and sebaceous and apocrine glands. Herein, we report a case along with detailed review of literature of this unusual disease.